INSTITUTIONAL MECHANISM OF HIGHER EDUCATION IN INDIA A SYSTEMS APPROACH - P. Sivaprakasam and S.M. Dhana Sundareswaran (Abhigyan, 2011)
The Indian higher education system, which consists of universities and colleges, is one of the largest higher education systems in the world. The universities in India are established either under an Act of Parliament in case of central universities and institutions that are recognized as central universities and thereby administered, regulated and funded by the apex higher education monitoring, funding and regulatory body namely the University Grants Commission (UGC) and other ministries of the Government of India. Universities are also established in the form of enacting a state legislature in case of state government universities. The deemed to be universities can be classified into two broad categories- one type is central deemed universities which are governed and funded primarily by UGC and other bodies and departments of Government of India whenever necessary. The others are largely self financing (Private) types. The universities and colleges could be measured to be a coordinating system and various departments and faculties of the universities could be deemed as sub-systems in higher education apparatus. These sub-systems are understood as components of the system. In order to augment the effectiveness of the system, feedback has been incorporated. Module one which pertains to inputs conveys a mixture of factors and issues for consideration in the higher education system. It may therefore contain factors such as objectives of university education, academicians / teachers, the students, the parents, infrastructural facilities, educational consultants, external and internal advisors, government policies and programmes, resources in the form of men, material, money, machinery, methods and so on and so forth. The bottom-line of any individual’s growth and development depends on how well he or she is educated and qualified in a certain direction which could help in betterment of the person concerned and of his society. In order to reach this end or goal, schools and colleges are considered as transforming and energizing centers of excellence where every individual will get the most of it in terms of acquiring knowledge, learning new things, involving in research and development and earning degrees. In this process the most important change agents are the academicians or simply teachers in any education system in the world. The academic people are therefore considered extraordinary. Output of the higher educational system includes availability of knowledgeable and trained human resources, science and technological improvement, socio-cultural changes in the country, infrastructural development for public usage, production of qualified human resources for job market, building a moral and ethical society, creating a knowledge society and production of trained entrepreneurs and potential leaders of industry. The fact that every individual registers into the university system with the notion of obtaining higher qualifications and certifications for the purpose of employment and status remains a universal phenomenon. The authors of this article have attempted to analyze higher education system in India in the form of systems approach or view incorporating inputs, transformation process and outputs encompassing all possible variables in the system